2010
DOI: 10.1186/1472-6963-10-69
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with health-seeking behavior among migrant workers in Beijing, China

Abstract: BackgroundMigrant workers are a unique phenomenon in the process of China's economic transformation. The household registration system classifies them as temporary residents in cities, putting them in a vulnerable state with an unfair share of urban infrastructure and social public welfare. The amount of pressure inflicted by migrant workers in Beijing, as one of the major migration destinations, is currently at a threshold. This study was designed to assess the factors associated with health-seeking behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
147
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(167 citation statements)
references
References 27 publications
15
147
4
1
Order By: Relevance
“…Families with high income are more possibly able to pay for migration. Particularly, due to the registered permanent residence policy in China, many parents may not be able to obtain not only pure air but also well education and health care though successfully migrate (Liang and Chen, 2007;Peng et al, 2010;Gong et al, 2012). Another Los Angeles Metro Region Study (Sieg et al, 2004) also confirmed our research and documented that when the application of the Clean Air Act successful reduced the smog level in certain communities, it attracted richer people living in inferior air condition to move to such area finally.…”
Section: Discussionsupporting
confidence: 76%
“…Families with high income are more possibly able to pay for migration. Particularly, due to the registered permanent residence policy in China, many parents may not be able to obtain not only pure air but also well education and health care though successfully migrate (Liang and Chen, 2007;Peng et al, 2010;Gong et al, 2012). Another Los Angeles Metro Region Study (Sieg et al, 2004) also confirmed our research and documented that when the application of the Clean Air Act successful reduced the smog level in certain communities, it attracted richer people living in inferior air condition to move to such area finally.…”
Section: Discussionsupporting
confidence: 76%
“…A similar finding was observed in a study in China, where major reasons for such a finding could be that migrants MSM, who had sex with females, may have more varied sexual behaviors with a wider range of sexual partners among both males and females [13]. Further, a cross-sectional study among migrant MSM in Beijing revealed that MSM who were involved in bisexual behavior had a higher proportion of unsafe sex with stable female partners and were less likely to take a part in preventive behaviors [14]. Therefore, any programme and intervention to address STI/HIV vulnerability among MSM, who are bisexual, there should a strong component of their capacity building to adopt safe sexual practices in one hand and enhancing women's empowerment to assess their partner's background and behavior to reduce their own vulnerability on the other.…”
Section: Discussionmentioning
confidence: 96%
“…A majority of our samples have the ability to buy or build their own houses in their hometown. In urban areas, most migrant workers live in rented houses on the city outskirts or in dormitory-style accommodations with public toilet facilities [51]. Houses in urban areas are generally too expensive for many migrant workers.…”
Section: Conclusion and Discussionmentioning
confidence: 99%